PENGABDIAN DESA UBEDOLUMOLO KABUPATEN NGADA NUSA TENGGARA TIMUR - Laga, Yulius; Doke , Herlina Theodenzia D (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Community Service Activities with the theme "Cultivating the Creative Spirit of Entrepreneurship in the Young Generation". We held in Ubedolumolo Village, Bajawa District, Ngada Regency. This activity was held from 10-12 August 2023, with the agenda of improving the community's economy by utilising local staple foods, painting village gates, creative activities from recycled materials to produce works for wall decorations and utilising land for planting agricultural products. The purpose of this activity is to provide training in the utilisation of local food into ready-to-sell products, the utilisation of bamboo and plastic waste into products with economic value and the utilisation of empty land with plants that are useful for local food. This activity is a form of participation between students and the community to increase understanding or knowledge, change behaviour and improve environmental conditions.